Intentions and barriers to using long-acting reversible contraceptives among young women seeking safe abortion care in Addis Ababa, Ethiopia: a qualitative study - Betelhem Simeneh Kabeto; Endalew Gemechu Sendo; Workinesh Sineshaw Abebe (BMC Public Health)
Abstract Background Long-acting reversible contraception (LARCs) including intrauterine devices and implants) are safe, highly effective, and recommended for adolescents, yet their use remains low. Reducing the number of repeat abortions can be achieved by improving family planning services after an abortion. Objective This study aimed to explore the perceptions, intentions, and barriers of young women seeking abortion care at the Family Guidance Association of Ethiopia (FGAE) regarding the use of LARCs in Addis Ababa, Ethiopia. Methods A qualitative exploratory study was conducted from February 20 to March 20, 2023. Sixteen young women seeking abortion services were selected using a purposive sampling method. Data collection involved the use of interview guides and in-depth interview techniques. The analysis incorporated both emergent inductive codes derived from the interview questions and a priori codes grounded in the theoretical framework. Results The data revealed three main themes: Young Women’s Perceptions of LARCs, Intentions to Use LARCs, and Perceived barriers. Conclusions This study’s findings provide valuable insights into young women’s perceptions, intentions and barriers regarding LARCs. Healthcare professionals and relevant stakeholders develop focused strategies that dispel myths, increase accessibility, and improve counseling on LARCs.